Popular physical education and sports in the volga federal district: progress analysis - Maksimov, D.G.; Anoshin, A.V.; Kotlyachkova, N.V.; Merzlyakova, A.Y. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze progress of popular physical education and sports in the Volga Federal District using cluster analysis. Methods and structure of the study. We applied for the purposes of the study a group of statistical data processing methods commonly referred to as the "learning without teacher", with a special application of a non-hierarchical clustering method with separation around k-medoids. Medoid means herein a centroid whose coordinates are shifted to the nearest input data array. We mined data for the study from the 2017-2020 reports of the Ministry of Sports of the Russian Federation. Results and conclusion. A comprehensive statistical data processing with cluster analysis made it possible to find the constituents of the Volga Federal District in need of special support in the popular physical education and sports encouragement initiatives. It should be mentioned that the Udmurt Republic has been ranked among the constituents still lagging behind in the physical education and sports committed population growth statistics for the last four years under study.